2008
DOI: 10.1099/jmm.0.2008/001107-0
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic evaluation of the effect of anaerobiosis on some virulence attributes of Candida albicans

Abstract: The current assumption that Candida albicans is a facultatively anaerobic organism has been widely accepted since its recovery from anoxic sites became common. However, the link between anaerobiosis and virulence remains uncertain. This study investigated the differential cell-surface hydrophobicity (CSH) using a hydrocarbon/water partition technique and analysed the differential secretion rates of secretory aspartyl proteases (Saps), esterase, chondroitinase and haemolysins of C. albicans strains recovered fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…This species is capable of anaerobic growth in the presence of L‐cysteine (Rosa et al. ) and AF. Importantly, we found that high anaerobic PYO toxicity was also elicited in C. albicans (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This species is capable of anaerobic growth in the presence of L‐cysteine (Rosa et al. ) and AF. Importantly, we found that high anaerobic PYO toxicity was also elicited in C. albicans (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The pathogenic crab-tree-negative yeast C. albicans was chosen because this fungus, together with Aspergillus fumigates, may coexist with P. aeruginosa in the lungs of cystic fibrosis (CF) patients (McAlester et al 2008). This species is capable of anaerobic growth in the presence of L-cysteine (Rosa et al 2008) and AF. Importantly, we found that high anaerobic PYO toxicity was also elicited in C. albicans (Fig.…”
Section: Candida Albicans Demonstrates Similar Pyo Sensitivity Under mentioning
confidence: 99%
“…, Rosa et al . ) have previously been investigated individually; however, there is a gap in knowledge in terms of starvation survival of C. albicans under anaerobic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Its prevalence has been estimated to be 6% and 18% (Peciuliene et al 2001, Rôças et al 2008. This dimorphic fungus grows well in the presence of molecular oxygen but less well under low oxygen tension and negative redox potentials (Rosa et al 2008). Its adaptability to adverse environmental conditions and ability to form biofilms under such conditions are crucial for survival in the nutrient-deprived environment such as those prevailing in cleaned and filled root canals (Siqueira & Sen 2004).…”
Section: Introductionmentioning
confidence: 99%
“…34 Research on TLR4 promoter methylation at CpG -646 and -822 positions in the gingival tissues showed that almost the whole subjects in the regions were not methylated and were not associated with TLR-4 mRNA transcripts. 35 Because all subjects were not methylated in the region target of the TLR4 promoter, it can be concluded that there was no correlation between the degree of methylation in the TLR4 target region with insulin resistance in adolescents with obesity.…”
Section: 142728mentioning
confidence: 95%